Interaction Between Murine Cardiac Stem Cells And Bone Marrow-Derived Mesenchymal Stem Cells For Cardiomyocyte Differentiation In Vitro - Leong, Yin Yee (2016)
Background: Bone marrow-derived mesenchymal stem cells (MSCs) has been shown to facilitate heart repair via activation of endogenous cardiac stem cells (CSCs) following infarction, but little is known if the synergy of the two cells can be exploited in vitro prior to transplantation. Objective: This study aimed to examine the synergistic effects of MSCs on CSC cardiomyocyte differentiation. Methods: C-kit CSCs and MSCs were isolated from 4-6 weeks C57BL/6N mice (n=9). CSC cardiomyocyte differentiation was tested after re-isolated from MSC co-culture using micron-sized particles of iron oxide, and compared to CSCs treated with MSC-conditioned medium (CdM) or without any treatment.